Spatial variability of available water and micro-sprinkler irrigation in cambisol - FERREIRA, LARISSA LUANA NICODEMOS (Revista Ceres, 2017)
The technology of irrigation is vital for agricultural production. Thus, description of spatial patterns of both water application and available water capacity in the soil, as well as their interactions, is essential to maximize efficiency of water use in irrigated areas. The objective of this study was to analyze spatial variability of available water capacity in the soil and water application via irrigation using geostatistics. The experiment was conducted in a commercial mango orchard in Cambisol irrigated by micro sprinkler system, in the municipality of Alto do Rodrigues, RN. Analyses of descriptive statistics and geostatistics were performed using the programs GeoR and GS+. Geostatistics was found suitable for describing the structure of spatial dependence of available water capacity in the soil and the flow rate distributed in the area by sprinklers. Moreover, even with good results for Christiansen Uniformity Coefficient (CU) and Distribution Uniformity Coefficient (DU), the area showed spatial variability of flow rate.